Design and Implementation of a 5G Radio Access Network Using srsRAN and Software Defined Radio (SDR) (Comprehensive Journal of Science, 2025)
This study focuses on the design and implementation of a 5G Radio Access Network(5G RAN) using open-source platforms, specifically srsRAN in combination with SDR devices,within a Standalone (SA) architecture. The functional split of the radio node was applied intoCU/DU/RU units, which were physically integrated with the core network through standardinterfaces (NG, F1). The experimental scenario involved connecting a virtual phone using SDR tothe radio network, thereby enabling the emulation of an end-user connection. The resultsdemonstrated successful registration and establishment of a PDU Session between the user and thenetwork, with stable performance observed in the downlink (DL), where appropriate CQI valueswere achieved alongside suitable data rates and nearly negligible error rates. In contrast, the uplink(UL) showed less stability due to the limited transmission power of the user equipment, as reflectedin fluctuating signal levels and higher error rates in certain cases. These findings confirm thefeasibility of deploying 5G RAN networks using open-source tools, offering a practical and flexibletestbed that not only supports academic research but also paves the way for future innovations innext-generation mobile networks.
Keywords: 5G, Radio Access Network (RAN), srsRAN, Software Defined Radio (SDR).